Answer:
b = -6
Explanation:
Apply the exponent rule that
In this case,
![(1)/(y^(24)) = y^(-24)](https://img.qammunity.org/2023/formulas/mathematics/college/m1hwmgksyiy7l5zb83jbgjax6zwfjypxol.png)
Set that equal to
:
![(y^(b))^(4) = y^(-24)](https://img.qammunity.org/2023/formulas/mathematics/college/cqbd7v0wcj9k5c90e1gskld5lltpncymx3.png)
Apply the exponent rule that
so now you get:
![y^(4b) = y^(-24)](https://img.qammunity.org/2023/formulas/mathematics/college/fupgavelqek5fsx4bxfi3t4wcss6qamai5.png)
Since the base is y for both sides of the equation, just set the exponents equal to each other and solve for b.
4b = -24
divide each side by 4 to get:
b = -6